Dose‐intensified bendamustine followed by autologous peripheral blood stem cell support in relapsed and refractory multiple myeloma with impaired bone marrow function. Issue 4 (18th March 2015) - Breitkreutz, Iris; Becker, Natalia; Benner, Axel.; Kosely, Florentina; Heining, Christoph; Hillengass, Jens; Egerer, Gerlinde; Ho, Anthony D.; Goldschmidt, Hartmut; Raab, Marc S.
Abstract: Therapeutic options in heavily pretreated relapsed/refractory multiple myeloma patients are often very limited because of impaired bone marrow function. Bendamustine is effective in multiple myeloma and has a favourable toxicity profile. We hypothesized that dose‐intensified bendamustine (180 mg/m 2, day 1 and 2) followed by autologous blood stem cell support (ASCS) would improve bone marrow function with low post‐transplant toxicity in patients with severely impaired haematopoiesis. We analyzed 28 consecutive myeloma patients, with a median of three prior lines of therapy (range 2–7), who had relapsed from the last treatment with very limited bone marrow function and were therefore ineligible for conventional chemotherapy, novel agents or trial enrolment. Dose‐intensified bendamustine with ASCS improved haematopoiesis as reflected by increased platelet counts (median 40/nl vs 94/nl, p = 0.0004) and white blood cell counts (3.0/nl vs 4.8/nl, p = 0.02) at day +100. The median time until engraftment of platelets (>50/nl) was 11 days (0–24 days) and of white cell counts (>1.0/nl) 0 days (0–24 days). At least, a minimal response was achieved in 36% of patients. The disease stabilization rate was 50% while the median progression‐free survival rate was limited to 2.14 months. Most importantly, patients were once again eligible for alternative treatments including enrolment into clinical trials. We conclude that dose‐intensified bendamustine followed by ASCS is safe and feasible for multiple myeloma patients with very limited bone marrow reserve. Copyright © 2015 John Wiley & Sons, Ltd.